Strengthening Hospital Competitiveness to Improve Patient Satisfaction and Better Health Outcomes 2019
DOI: 10.26911/the6thicph-fp.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurse Theraupetic Communication on Satisfaction among The Families of Schizophrenic Patients at Prof Muhammad Ildrem Mental Hospital, Medan, North Sumatra

Abstract: Background: Therapeutic communication is the primary component of all health care interaction that facilitates the development of positive clinician-patient experiences. Nurses with the skills to communicate not only will be easily establish a trusting relationship with the patients but also patients' families. Therapeutic communication is known to be necessary for quality healthcare and increase patient satisfaction. This study aimed to examine the effect of nurse therapeutic communication on satisfaction amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This study was in line with Sumah et al (2013) Similar study was also conducted by Yeni (2013), with the title Factors Affecting Household Waste Management in the Village Village of Johan Pahlawan District, West Aceh, the results showed that knowledge and attitudes had a relationship with household waste handling so that there was a significant relationship between knowledge and attitude with the handling of household waste in Gampong Darat Village, Johan Pahlawan District, West Aceh.…”
Section: The Effect Of Attitude On Waste Managementsupporting
confidence: 90%
“…This study was in line with Sumah et al (2013) Similar study was also conducted by Yeni (2013), with the title Factors Affecting Household Waste Management in the Village Village of Johan Pahlawan District, West Aceh, the results showed that knowledge and attitudes had a relationship with household waste handling so that there was a significant relationship between knowledge and attitude with the handling of household waste in Gampong Darat Village, Johan Pahlawan District, West Aceh.…”
Section: The Effect Of Attitude On Waste Managementsupporting
confidence: 90%